2010
DOI: 10.1111/j.1365-3180.2010.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

The response of Bromus diandrus and Lolium rigidum to dalapon and glyphosate I: baseline sensitivity

Abstract: The establishment of Bromus diandrus and Lolium rigidum baseline sensitivity to glyphosate and dalapon herbicides was studied for the North Central region of Spain. A rapid method in Petri dishes and a plant assay method were evaluated. The studied populations of both weed species showed sensitivity to both herbicides. The rapid method to establish the sensitivity baseline for these species worked properly for dalapon and a good correlation was found between Petri dish and plant assays. In the case of glyphosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Barroso et al . () collected five populations each of Lolium rigidum and Bromus diandrus Roth (ripgut brome), all with no previous glyphosate exposure, and reported I 50 values ranging between 17–46 g a.i. ha −1 and 85–117 g a.i.…”
Section: Discussionmentioning
confidence: 99%
“…Barroso et al . () collected five populations each of Lolium rigidum and Bromus diandrus Roth (ripgut brome), all with no previous glyphosate exposure, and reported I 50 values ranging between 17–46 g a.i. ha −1 and 85–117 g a.i.…”
Section: Discussionmentioning
confidence: 99%
“…Other sensitivity studies revealed factors between ED 50 's of the most and the least sensitive populations of 4.9 [15 Papaver rhoeas populations tested with florasulam in different European countries (Paterson et al ., )] and 1.4–2.7 [six Bromus diandrus Roth and five Lolium rigidum Gaudin populations tested with dalapon and glyphosate in north Spain (Barroso et al ., )]. Already in 1975, genetic variation of T. inodorum to MCPA was investigated in populations coming from southern Britain and northern France (Ellis & Kay, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the level of non-target-site resistance can be rather low, which makes it difficult to separate low non-target-site resistance from the background variability in sensitivity. Baseline and sensitivity monitoring are essential in resistance management (Ulber et al, 2013), but few data are available in the scientific literature (Paterson et al, 2002;Roux et al, 2005;Barroso et al, 2010).…”
Section: The European and Mediterranean Plant Protectionmentioning
confidence: 99%
“…As defined in the EPPO standard, data on the sensitivity variation among weed populations can only be considered as a baseline if they are obtained from populations that have never been exposed to the herbicide or to related active substances with the same mode of action. Baseline sensitivity data can be generated before the initial introduction of a herbicidal active substance, therefore allowing the evaluation of changes in sensitivity to the herbicide and thus the detection, at an early stage, of any trend towards resistance , . This is especially important for the detection of non‐target‐site resistance where resistance evolves as a slow (‘creeping’) shift of increased mean resistance level with each subsequent generation .…”
Section: Expectations Versus Reality— Sensitivity Data In the Europeamentioning
confidence: 99%